Governing Tourism Destination with Innovation System in Malang Regency - Dwi Meylani, Nanda; Kusdi, Kusdi; Abdillah, Yusri (Graduate School, Universitas Brawijaya, 2020)
This research is a descriptive qualitative research that seeks to obtain a new perspective and describe tourism destination governance based on the innovation system in tourism in Malang Regency. The types of data in this study are primary data and secondary data. The researcher collected data using interviews, observation, and documentation. Data is analyzed by carried out throughout the research process, including the preparation of data management and data collection. The conclusion is carried out continuously by looking for patterns, themes, relationships, explanations, and causal paths regarding the results of research on tourism destination governance. The results indicate several problems that must be solved, such as the lack of tourism promotion, the lack of community involvement, limited material for tourism exhibition, and mismatch in tourism development. To solve the problems, the government must strengthen SIDa (Regional Innovation System), which consists of a strategic pillar and policy framework.Keywords: governance, innovation systems, tourism destinations.